1984
DOI: 10.1111/j.1476-5381.1984.tb10736.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced responsiveness of rat isolated aorta to clonidine after removal of the endothelial cells

Abstract: With the endothelium present, the maximum response of rat isolated aorta to clonidine was much lower than that to noradrenaline. Removal of endothelium enhanced the response to both adrenoceptor agonists and the clonidine-induced maximum contraction became almost equal to that produced by noradrenaline, although it was much more sensitive to inhibition by flunarizine and nifedipine. These results indicate that clonidine and noradrenaline activate receptors present in the endothelial cells and that these recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
1
3

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(94 citation statements)
references
References 5 publications
10
80
1
3
Order By: Relevance
“…70Mm diameter can be adequately resolved (Griffith et al, 1988). Haemoglobin appears to be a specific inhibitor of EDRF activity at the concentration employed (1 gM) (Martin et al, 1985;Edwards et al, 1986;Kelm et al, 1988;Nishiye et al, 1989 (Cocks & Angus, 1983;Miller & Vanhoutte, 1985;Egleme et al, 1984;Matsuda et al, 1985), there is no evidence that al-adrenoceptors can do so in any species or artery type. The lack of effect of haemoglobin in the absence of a constrictor agonist in this preparation differs from previous experiments with the rabbit isolated ear, in which inhibition of basal EDRF activity induced a small but significant rise in perfusion pressure in the absence of exogeneous constrictor agents and in which haemoglobin therefore unmasked myogenic tone (Griffith et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…70Mm diameter can be adequately resolved (Griffith et al, 1988). Haemoglobin appears to be a specific inhibitor of EDRF activity at the concentration employed (1 gM) (Martin et al, 1985;Edwards et al, 1986;Kelm et al, 1988;Nishiye et al, 1989 (Cocks & Angus, 1983;Miller & Vanhoutte, 1985;Egleme et al, 1984;Matsuda et al, 1985), there is no evidence that al-adrenoceptors can do so in any species or artery type. The lack of effect of haemoglobin in the absence of a constrictor agonist in this preparation differs from previous experiments with the rabbit isolated ear, in which inhibition of basal EDRF activity induced a small but significant rise in perfusion pressure in the absence of exogeneous constrictor agents and in which haemoglobin therefore unmasked myogenic tone (Griffith et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Such a role for the vascular endothelium has also been reported in human isolated vessels, particularly human coronary arteries (Thom et al, 1985;Bossaller et al, 1986;Forstermann et al, 1986b). In addition, the presence of endothelium can modulate agonist-induced contractile responses of some animal arteries (Cocks & Angus, 1983;Egleme et al, 1984;Miller et al, 1984;Lues & Schumann, 1984;Godfraind et al, 1985;Carrier & White, 1985;Miller & Vanhoutte, 1985), probably as a consequence of a spontaneous release of ('basal') EDRF (Malta et al, 1986a;Martin et al, 1986). To date, there has been no evidence for basal release of EDRF in human isolated arteries.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that agonist-induced contractions of vascular smooth muscle which are relatively resistant to the modulatory effect of the endothelium are also relatively resistant to the effect of calcium entry blockers (Egleme et al, 1984;Godfraind et al, 1985). Therefore it has been proposed that EDRF could affect receptor-operated Ca2 +-gating in vascular smooth muscle (Godfraind, 1986).…”
Section: Contractile Experimentsmentioning
confidence: 99%
“…In cat arteries subjected to either extra-or intraluminal NE, the E max was also substantially A few years ago, Furchgott and Zawadzki (1980) showed that the presence of the endothelium was an essential condition for obtaining relaxation of rabbit thoracic aorta strips in response to acetyl choline. Since then, many studies have confirmed the essential role of the endothelium in vasodilata tions induced by various agents and in a variety of preparations [see Furchgott (1983) for review].In contrast to this burgeoning literature on dilator agents, very few reports (e.g., Cocks and Angus, 1983;Egleme et al, 1984) have appeared on con strictor agents and the influence of the endothelium, and none deal with cerebral vessels. It seemed im portant to us to determine whether vasoconstrictor responses in the cerebral circulation could be influ enced by the vascular endothelium since naturally occurring agents such as norepinephrine (NE) and serotonin are known to be released during (patho)physiological phenomena such as vaso spasm (du Boulay et aI., 1983;Cook, 1984) of any kind of lesion or alteration of the endothelial lining such as is present in atherosclerosis.…”
mentioning
confidence: 99%
“…In contrast to this burgeoning literature on dilator agents, very few reports (e.g., Cocks and Angus, 1983;Egleme et al, 1984) have appeared on con strictor agents and the influence of the endothelium, and none deal with cerebral vessels. It seemed im portant to us to determine whether vasoconstrictor responses in the cerebral circulation could be influ enced by the vascular endothelium since naturally occurring agents such as norepinephrine (NE) and serotonin are known to be released during (patho)physiological phenomena such as vaso spasm (du Boulay et aI., 1983;Cook, 1984) of any kind of lesion or alteration of the endothelial lining such as is present in atherosclerosis.…”
mentioning
confidence: 99%